ANALYSIS OF THE POETRY OF HENRY WADSWORTH LANGFELLOWS A PSALM OF LIFE (STRATA ROMAN INGARDEN) - Islami, Suci Nur (Universitas Suryakancana, 2023)
This research analyses poetry using Roman Ingarden's Srata. In this research, descriptive quantitative method is used because the data used are words. In analysing the poem A Psalm of Life, the descriptive descriptive research method is used with the Roman Ingarden stratum approach and the literature study analysis technique. In the stratum of romance ingarden itself there are five layers of norms, namely the layer of sound, the layer of meaning, the layer of objects, the layer of the world, and the metaphysical layer. In the second layer there are meanings which result from this layer of meaning found the next layers which indicate that each layer is a whole structure. The conclusion from the research that has been done is that the poem A Psalm Of Life by Henry Wardswort Langfellow has all the layers of sound, meaning, object, world, and metaphysical norms. However, not all poems have metaphysical layers.